2023
DOI: 10.1186/s13765-023-00785-3
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation characteristics and radical scavenging capacities of ginseng berry kombucha fermented by Saccharomyces cerevisiae and Gluconobacter oxydans

Abstract: Kombucha is a healthy carbonated beverage made by fermenting tea extracts such as green tea and black tea through symbiotic culture of bacteria and yeast. In this study, fermentation characteristics and radical scavenging activity of ginseng berry kombucha (GBK) by Saccharomyces cerevisiae M-5 and Gluconobacter oxydans were measured. As fermentation time increased, pH decreased and titratable acidity increased. Reducing sugars decreased rapidly on day 3. Alcohol content increased dramatically during this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A previous study reported similar biological features, where the antioxidant activities of ginseng berry-derived kombucha from different fermentation times were evaluated. 52…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported similar biological features, where the antioxidant activities of ginseng berry-derived kombucha from different fermentation times were evaluated. 52…”
Section: Resultsmentioning
confidence: 99%